Application of calcium overload-based ion interference therapy in tumor treatment: strategies, outcomes, and prospects - Li, Shuangjiang; Fan, Ruicheng; Wang, Yuekai; He, Kunqian; Xu, Jinhe; Li, Hongli (Frontiers in Pharmacology, 2024)
Low selectivity and tumor drug resistance are the main hinderances to conventional radiotherapy and chemotherapy against tumor. Ion interference therapy is an innovative anti-tumor strategy that has been recently reported to induce metabolic disorders and inhibit proliferation of tumor cells by reordering bioactive ions within the tumor cells. Calcium cation (Ca 2+ ) are indispensable for all physiological activities of cells. In particular, calcium overload, characterized by the abnormal intracellular Ca 2+ accumulation, causes irreversible cell death. Consequently, calcium overload-based ion interference therapy has the potential to overcome resistance to traditional tumor treatment strategies and holds promise for clinical application. In this review, we 1. summed up the current strategies employed in this therapy; 2. described the outcome of tumor cell death resulting from this therapy; 3. discussed its potential application in synergistic therapy with immunotherapy.